The best of Active Training II : (Pfeiffer, 2008)
Do you want to create training experiences that will heighten participation, help trainees better retain the information presented, and encourage application? Now it’s easy turn your training up a notch and to put excitement into your programs with The Best of Active Training II. Like its predecessor The Best of Active Training I, The Best of Active Training II is a unique resource that substantially lessens the time required. It allows any trainer to examine 25 state-of-the-art workshop designs, covering the training topics most currently in demand. The training professional can then select those designs that can be used as-is, with little or no modifications, as well as those that can be easily customized for special circumstances.